2023
DOI: 10.1155/2023/1930093
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent COVID-19 Waves and Lockdown: Impact on Daily Life and Mental Health of People in Nepal

Abstract: Background. Lockdown is recognized as an effective measure in limiting the spread of coronavirus (COVID-19) throughout the world. However, recurrent COVID-19 infection and the extension of lockdown have threatened the livelihoods of people, mainly socioeconomic and mental health dimensions. Objective. The present study is aimed at identifying the impact of COVID-19 lockdown on the daily life and mental health of the general population of Nepal. Furthermore, the study identified the predictors of the mental hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Informal caregivers of COVID-19 faced their own exposure risks and increased concerns about self-care and health. When the patient with signs of severe COVID-19 needed hospitalization, caregivers experiences a mix of positive and negative experiences including stigma, change in relationships, fear of contracting the disease, psychological stress, visitation restrictions, economic worries, and grieving, making the caregiving task even more challenging [12][13][14]. Additionally, several studies indicated that caregivers experienced social isolation, chronic stress, psychological distress, and physical and mental health problems exacerbated by the contagious nature of COVID-19 [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Informal caregivers of COVID-19 faced their own exposure risks and increased concerns about self-care and health. When the patient with signs of severe COVID-19 needed hospitalization, caregivers experiences a mix of positive and negative experiences including stigma, change in relationships, fear of contracting the disease, psychological stress, visitation restrictions, economic worries, and grieving, making the caregiving task even more challenging [12][13][14]. Additionally, several studies indicated that caregivers experienced social isolation, chronic stress, psychological distress, and physical and mental health problems exacerbated by the contagious nature of COVID-19 [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Informal caregivers of Covid 19 had their own COVID-19 exposure risks and concomitant increased concerns about selfcare and health. As the patient with signs of severe COVID-19 need to be hospitalized, caregivers experienced a collection of positive and negative experiences such as stigma, change in relationships, fear of contracting disease, psychological stress, visitation restrictions, economic worries and grieving, which made the caregiving task harder to accomplish (12) (13) (14). Further, several studies established that caregivers faced social isolation, chronic stress psychological distress and physical and mental health problems exacerbated by contagious nature of COVID-19.…”
Section: Introductionmentioning
confidence: 99%